Nutritional status of school going children and adolescents aged 9-13 years at Haldia in West Bengal, India - Sudip Datta Banik; Soumita Chatterjee (Paediatrica Indonesiana, 2010)
Background Malnutrition in children and adolescents is a globalÂ problem. In developing nations of Africa and Southeast Asia,Â the prevalence of undernutrition in children is very high. ThereÂ is scanty data 'With respect to the nutritional status of schoolÂ going children and adolescents, especially from subô€‰urban andÂ rural areas in India.Objective A study was undertaken among boys (n = 174) and girlsÂ (n = 128) aged 9ô€‰ 13 years in a subô€‰urban area of Purba MedinipurÂ district of West Bengal in India to understand age and sex variationÂ of nutritional status of the subjects.Methods A crossô€‰sectional study among the schoolô€‰going childrenÂ and adolescent aged 9ô€‰ 13 years was done during Juneô€‰SeptemberÂ 2009 in Haldia.Results Age and sex variation of anthropometric characteristicsÂ (body mass index or BMI and conicity index or CI) revealedÂ that remarkable sections of both the sexes were suffering fromÂ underweight (8.30%), stunting (14.60%) and wasting (2.80%).Â Significant sex differences were observed in cases of mean CIÂ (P=O.OO1), weightô€‰forô€‰age zô€‰score (P = 0.0001) and weight-for-height ,-score (P ô€€‚ 0.0001).Discussion Besides notable prevalence of under nutrition in bothÂ sexes, situation of the girls is worse (underweight - 11.70% andÂ stunting - 21.10%) compared to the boys. This is most evidentÂ among the subjects of both sexes aged 11 and 12 years.Â Â Â